Penerapan Sistem Point Of Sale Berbasis Android Untuk Peningkatan Kinerja Usaha - Putra, Handhira Bayu Pradhana; Sancoko, Sulistyo Dwi (Fakultas Teknik Universitas Hamzanwadi, 2024)
Micro, Small and Medium Enterprises in Presidential Decree No. 99 of 1988 are small-scale people's economic activities with business fields that are mostly small business activities. However, in MSMEs, there are several types of obstacles including data collection of stock of goods, transaction reports and financial statements that are not effective and efficient. Therefore, researchers want to change the way store management uses modern methods by designing a point of sale system as an android-based platform for MSMEs Established Stores. Point of Sales systems help various retail businesses make buying and selling transactions quickly, safely, and systematically. POS also includes modern cash registers commonly used in some stores or businesses. The design of this system uses technology from Firebase, namely the Realtime Database feature. The result of this study is an android-based point of sale application. Point of sale applications can simplify the management process at Established Stores. This can be seen from the system testing with the blackbox method which gets good results and all functions run well